DIGITAL LITERACY ASSISTANCE IN THE UTILIZATION OF SOCIAL MEDIA FOR COMMUNITY MICRO-ENTERPRISES AT THE GUNA RAYADI ILMU COURSE AND TRAINING INSTITUTE - Saddam; Fahmi Hanifa; Yonoriadi; Riyan Maulana; Saprijal; Evi Mauliza; Muhammad Falik Arsa; Muhammad Yassir; Rahmat Arfan; Joharsah; Nasruddin (Jurnal Pengabdian Bangsa, 2026)
Developing digital literacy is crucial in facing the era of globalization and the rapid digital transformation. Digital literacy encompasses not only the ability to access information through technology, but also the skills to understand, manage, and utilize it wisely in accordance with prevailing norms , ethics, and culture. This community service program aims to improve digital literacy as a means of community empowerment at the Guna Rayadi Ilmu Course and Training Institute, particularly in the Micro, Small, and Medium Enterprises (MSMEs) and tourism sectors. The methods used include a descriptive approach through literature studies, field observations, and interviews with MSMEs and village communities involved in e-commerce activities. The results of the activity indicate that limited understanding of digital technology remains a major obstacle in accessing digital economic opportunities in villages. Through digital literacy training and mentoring, communities are beginning to understand the use of technology for promoting local products, conducting online transactions, and managing e-commerce-based businesses. This program has had a positive impact on increasing local economic capacity, expanding marketing networks, and reducing digital-based social disparities. Thus, digital literacy has proven to be a strategic instrument in empowering rural communities towards inclusive and sustainable economic development.